CFD simulation of direct chill casting process of magnesium alloy billets - Lee, Wei Loon; Sreekar Reddy, S.; A. K., Prasada Rao (Elsevier Ltd, 2019)
This work demonstrates and simulates the industry scale direct chill casting of magnesium alloy (AZ31) billets processed under various conditions. The solidification mechanisms involved the conventional and melt-conditioned direct chill casting processes are simulated using the computational fluid dynamics. The heat flow and the solid-liquid interface are clearly identified for various casting speeds, depth of the rotor-stator device and the device geometry. The results also indicate that the shape and depth of the solid-liquid interface sump is sensitive to the casting parameters.